Stadsdelsparken Skälby i Kalmar - Johansson, Emma (2008)
Skälby park is situated approximately 2,5 km northwest of the central parts of Kalmar and is one of fi ve town part parks. Originally Skälby consisted of a village of four farms. In 1965 the municipality in Kalmar bought Skälby and the agriculture ceased to appear. The land was parcelled out into plots and new roads. Only the area surrounding the old buildings remained, turned to a park. The park has a rural simplicity refl ecting the agriculture. The area has a value of cultural history with the manor house from the 18th century and old pastures with great nature and recreational values. Today activities like 4H, logdans, outdoor concerts take place in the park. Also you fi nd the city's largest playground here. This thesis aims to develop concepts and strategies for the park, which in many reasons can be seen as a left-over from the small-scale agriculture society. In order to get the comprehensive picture statistics over adjacent housing areas, the park according to Kalmar's green structural planning, a history description and an inventory's and analysis part is presented. The inventory's - and the analysis part is treated the park's physical structure and how the park is experienced from recreational, safety's and playing perspectives. Based on knowledge from the above parts, concepts and strategies are developed for the park. These strategies aim to: • Let the agricultural history become apparent • Create a stronger contact with adjacent housing areas • Create a functional moving pattern • Develop the rural character of the park • Develop a park with many experiences • Develop the accessibility of the park • Create safe environments • Create challenging environments for playing accessible for everyone